Tick-Borne Viral Encephalitis Morbidity Rates in the Constituent Entities of the Russian Federation. Communication 1: Epidemiological Situation on Tick-Borne Viral Encephalitis in 2018 and Forecast for 2019 - A. K. Noskov; E. I. Andaev; A. Ya. Nikitin; N. D. Pakskina; E. V. Yatsmenko; E. V. Verigina; M. I. Tolmacheva; S. V. Balakhonov (Проблемы особо опасных инфекций, 2019)
Epidemiological situation on tick-borne viral encephalitis in the Russian Federation in 2018 was analyzed. Dynamics of the incidence, medical aid appealability among persons who suffered from tick suction, virus carriage of the vector; vaccination volumes, seroprophylaxis; acaricide treatment are reported in the paper. Utilized were the data on operative monitoring performed by the Rospotrebnadzor Institutions in the constituent entities of the Russian Federation and form data from the Federal statistical survey «Data on Infectious and Parasitic Diseases» over the period of 2009–2017, and also information from the operative monitoring, 2018. The increase in medical aid appealability among the population due to tick suctions was observed in all endemic Federal Districts (FD) of the European part of the Russian Federation during the epidemic season, 2018. The total of 1508 cases in 46 constituent entities of the country was registered: Siberian FD – 44.3 % of the cases, Privolzhsky FD – 22 %, Ural FD – 14.7 %, Northwest FD – 12.6 %,Central FD – 3.7 % , and Far Eastern FD – 1.7 %. Twenty two cases had lethal outcomes. Nation average infection rate of ticks taken off from humans was 1.38 %, from environment objects – 0.61 %. General level of tick infectivity was 1.5 times lower in 2018 as compared to 2017. The forecast of the incidence for 2019, taking into account the presence or absence of the trend fluctuations in the constituent entities in 2009–2018 and the values of the 95 % confidential interval of the possible parameter variations, is presented. The further gradual improvement of the epidemiological conditions for tick-borne viral encephalitis is expected. According to estimates, in 2019, morbidity rates will be 0.19 0/0000 in CentralFD, with value fluctuations ranging between 0.128 to 0.247 cases, in Northwest FD – 1.12 0/0000 (0.112 to 2.122 0/0000), Privolzhsky FD – 0.67 0/0000 (0↔1.649), Ural FD – 1.2 0/0000 (0↔4.590), Siberian FD – 3.4 0/0000 (1.319↔5.471), and Far Eastern – 0.65 0/0000 (0.522↔0.770).